2007
DOI: 10.1097/01.hp.0000244086.36815.7c
|View full text |Cite
|
Sign up to set email alerts
|

Demodulation in Tissue, the Relevant Parameters and the Implications for Limiting Exposure

Abstract: In the biomedical literature there are a number of reports that speculate about possible effects in the body due to the demodulation of electromagnetic fields. However, only few interactions in amplitude-modulated or even pulse-modulated electromagnetic waves are fundamentally plausible and have been demonstrated to occur in humans. The following observations fall into this specific category: thermal effects of amplitude- or pulse-modulated microwaves; demodulation of amplitude- or pulse-modulated electromagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Biophysical theory (Pickard and Rosenbaum 1978) and experiments in plant cells (Barsoum and Pickard 1982) showed that in the absence of heating, nonlinear behavior at cell membranes does not occur above approximately 10 MHz. These findings should apply to animal cells too, as was demonstrated by experimental data from human subjects tested for nerve stimulation thresholds as a function of frequency (Silny 2007). A single pulse of up to 100 ms duration was used over a range of RFs to determine whether there would be a response to modulated signals at each frequency.…”
Section: Nonlinearity Generates Harmonic Frequencies and Demodulationmentioning
confidence: 97%
See 1 more Smart Citation
“…Biophysical theory (Pickard and Rosenbaum 1978) and experiments in plant cells (Barsoum and Pickard 1982) showed that in the absence of heating, nonlinear behavior at cell membranes does not occur above approximately 10 MHz. These findings should apply to animal cells too, as was demonstrated by experimental data from human subjects tested for nerve stimulation thresholds as a function of frequency (Silny 2007). A single pulse of up to 100 ms duration was used over a range of RFs to determine whether there would be a response to modulated signals at each frequency.…”
Section: Nonlinearity Generates Harmonic Frequencies and Demodulationmentioning
confidence: 97%
“…A single pulse of up to 100 ms duration was used over a range of RFs to determine whether there would be a response to modulated signals at each frequency. Unlike lower frequencies, at 10 MHz the required amplitude of the RF electric field was so large that the pain threshold was reached before being able to observe nerve stimulation indicative of demodulation (Silny 2007).…”
Section: Nonlinearity Generates Harmonic Frequencies and Demodulationmentioning
confidence: 99%
“…The applied signal has synergy with the heating of the extracellular matrix, constructing zero-mode noise component which surpasses the thermal noise [1]. The "demodulation" of the noise [2] uses the ratchet mechanism [3] and the stochastic resonance phenomena [4] combined with the membrane rectification [5] and nonlinearity [6]. The applied time-fractal modulation is one of the specialties, which only oncothermia has in hyperthermia applications in oncology.…”
Section: Introductionmentioning
confidence: 99%